Kepemimpinan Perempuan Dalam Perspektif Fiqh Siyasah - Amelia, Rizky; Azzahra, Rachel Sabina; Panjaitan, Zayyan Tsabitah; Witra, Layla; Pohan, Nurul Fattah (Tabayyun : Journal Of Islamic Studies, 2023)
Women's leadership in politics is still a matter of debate among the ulama. On the one hand, most ulama do not give rights to women unless it is forbidden for them to become political leaders. They refer textually to the Koran, surah al-Nisa' verse 34, and the hadith narrated by Abi Bakrah. However, on the other hand, some Muslim reformers allow it on the grounds that there has been an accumulation of extraordinary social changes so that women today are considered relatively equal to men. This article aims to try to describe the two groups of ulama's opinions, then analyze their thinking historically and contextually, as well as provide an assessment by reconstructing old thinking to adapt it to the current context. Mufassir and fiqh scholars in the past tended to interpret verses and understand hadiths with a gender bias. This was because apart from the culture that surrounded them at that time, the position of women at that time was also very backward in various fields. Such interpretation and understanding have received a response from contemporary Muslim reformers and thinkers who try to interpret verses and understand hadith contextually. They see that women have the right to be leaders, and in reality it is proven that some women have the same abilities and expertise as men. This means that political leadership is not related to male or female gender, but is related to the capacity and abilities that must be possessed.